Alignment of learning experiences from prekindergarten to kindergarten: Exploring group classifications using cluster analysis. (September 2018) - Franko, Meg Deane; Zhang, Duan; Hesbol, Kristina
This study explored children's experiences of instructional alignment from prekindergarten through kindergarten. Using cluster analysis to analyze data from over 1300 children in the 2009 Head Start Family and Child Experiences Survey, the study found that children have distinct and definable experiences of prekindergarten–kindergarten alignment, with Hispanic/Latino children more likely to attend Head Start programs with poor support for prekindergarten–kindergarten transitions and poor kindergarten classroom structures, and most children experiencing a decline in developmentally appropriate practices between prekindergarten and kindergarten.